Analysis of emergency department waiting time evidence from a tertiary hospital in Indonesia: A qualitative study - Alouw, Christy Natalia; Kaunang, Erling David; Homenta, Heriyannis (Institute of Computer Science (IOCS), 2025)
Prolonged waiting times in the Emergency Department caused by high patient volume, limited resources, and operational inefficiencies. This study aims to identify and analyze the factors contributing to waiting times in the Emergency Department. This qualitative descriptive study was conducted over three months (March to May 2025) in the Emergency Department of Prof. Dr. R. D. Kandou General Hospital, Manado. Participants including hospital leadership, emergency physicians, nurses, and the ED head were purposively selected. Data were gathered through semi-structured interviews, direct observations, and patient flow data from the electronic medical records dashboard. Analysis used triangulation to identify patterns and factors influencing waiting times. Emergency Department employs a triage system prioritizing patients by urgency, but faces challenges such as high patient volume, limited staffing and beds, technical issues, and communication delays. Despite efforts to reduce waiting times, critically ill patients often exceed recommended ED stays due to complex care needs. Continuous improvements focus on increasing staff, enhancing infrastructure and information systems, strengthening coordination, and educating the public to optimize patient flow and service quality. Despite effective triage and digital queue systems, persistent staffing, infrastructure, and coordination challenges continue to limit ED efficiency, so improving these areas is essential to enhance performance.